Pada Konsep Penganiayaan Berat Sebagai Penghalang Kewarisan Dalam KHI - Muhammad, Mar'i; Fitri, Nurul Amalia; Maloko, M. Thahir; Hasan, Hamzah (Media Hukum Indonesia (MHI), 2025)
In the Compilation of Islamic Law (KHI), Article 173 states that a person who kills or attempts to kill an heir, is not entitled to receive an inheritance. Nevertheless, in judicial practice, issues arise on the application of the concept of “serious mistreatment” as a form of action that obstructs heir rights. The term is often used to refer to acts of violence that have not necessarily caused death, but are nonetheless considered severe enough to disfranchise someone. Unfortunately, the KHI does not provide clear restrictions or definitions regarding what is meant by “severe persecution”. This raises questions from the point of view of the principles of legal clarity and certainty, which are fundamental principles in national legal systems. The concept of severe persecution as a barrier to inheritance in the KHI has strong moral and philosophical urgency because it is aligned with the values of justice and maqashid al-shari’ah. However, in the context of positive legal norms, the term still harbors fundamental questions in terms of redactional clarity and certainty of application. The absence of a clear normative definition in the KHI leaves the term “severe maltreatment” prone to being interpreted subjectively by individual judges. As a result, inconsistencies occur in court judgments, which ultimately harm the parties seeking justice. From the perspective of the basis of legal clarity, legal norms are supposed to be formulated in language that is concrete and easy to understand. Whereas from the grounds side of legal certainty, the norm must be consistently enforceable and immutable.